The Effect of Exercise Program on Low Back Pain Preventive Behaviors in Pregnant Females Referred to Health Centers of Karaj - Maryam Khalednejad; Sedighe Tavafian; Shamsodin Niknami (Journal of Education and Community Health)
Background and Objectives: Back pain is the most common pain in pregnancy. This research aimed at exploring the influence of exercise program training on behavior change that leads to back pain prevention in pregnant females.